AUDITOR INDEPENDENCE AND AUDIT QUALITY: EMPIRICAL EVIDENCE FROM QUOTED OIL AND GAS FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
This study examines auditor’s independence and audit quality in Nigeria’s oil and gas sector. Two research hypotheses were formulated for the study. This study made use of ex-post facto research design. The data for the study where obtained from annual reports and accounts for the period. The data were analyzed using binary logit regression with the aid of E-views, 9.0. The results showed that the proxies of auditor independence; audit fee and audit tenure were both positive; but, only audit fee was statistically significant. The study recommends among others that audit firms are selected based on the tripartite characteristic of experience, exposure and specialisation. This study has implications for shareholders in determination of audit quality thereby safeguarding shareholder wealth.
Keywords: audit independence; auditor tenure; audit fee; auditor quality